A web aided education model that can be used in power electronics course - KANBUROĞLU, VOLKAN; BİRBİR, YAŞAR (ELSEVIER - DIVISION REED ELSEVIER INDIA PVT LTD, 2018)
In this study, the effect of web based power electronics courses on the success of electrical engineering candidates was examined. The participants are consisted of daytime education (30) and evening education (42) students who attended the Power Electronics course. First, groups were randomly assigned as experimental and control groups and experimental group and control group were examined according to the students' GPAs, university entrance exam results, academic grades depending on 8 different lectures related with power electronics. According to the results obtained from validity and reliability of Power Electronics Course Achievement Test, the total correlation values and the standard deviation values of Power Electronics Course Achievement Test were between.301-,.598 and between.304-,.506, respectively. In addition, KR20 coefficient was found as 0.844. Before application of the Power Electronics Course Achievement Test, there was not a significant difference in total scores of both daytime and evening education students. Although students received Web-Based Education and Web Aided Education were selected as experimental group, the students received Traditional Education were selected as control group. After the application, significant differences between the total grade points of both experimental and control groups of daytime education and evening education students were detected. (C) 2018 Karabuk University. Publishing services by Elsevier B.V.
Keywords: Distance learning; Electronic learning; Learning management systems; Open source hardware; Visual communication; DESIGN